1993
DOI: 10.1021/j100107a008
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio MO studies on disilane, germylsilane, and digermane radical anions as prototypes of polymer anions with silicon and germanium backbones

Abstract: Disilane, silylgermane, and digermane radical anions have been studied by ab initio molecular orbital theory, using the unified level of basis set as prototypes of polymer anions with Si and Ge backbones. These prototype anions have the same kind of minimum geometry (C2/, or C2*-like symmetry) with an unpaired electron occupying the Si-Si, Si-Ge, or Ge-Ge a* antibonding orbital with a large Si or Ge s diffuse orbital contribution. Little Si 3d or Ge 4d orbital participation is found for these anions. All these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 4 publications
5
14
1
Order By: Relevance
“…Our predicted adiabatic electron affinities for Ge 2 H 6 are negative, for instance −0.19 eV (or −0.02 eV after ZPVE correction) with B3LYP (Table 4), and the anion is thus unbound. Tada and Yoshimura earlier predicted that the adiabatic electron affinity40 is much more negative (−0.78 eV), but still in qualitative agreement with our results. No experimental electron affinity has been observed, as is the case for C 2 H 6 and Si 2 H 6 .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Our predicted adiabatic electron affinities for Ge 2 H 6 are negative, for instance −0.19 eV (or −0.02 eV after ZPVE correction) with B3LYP (Table 4), and the anion is thus unbound. Tada and Yoshimura earlier predicted that the adiabatic electron affinity40 is much more negative (−0.78 eV), but still in qualitative agreement with our results. No experimental electron affinity has been observed, as is the case for C 2 H 6 and Si 2 H 6 .…”
Section: Resultssupporting
confidence: 93%
“…Our theoretical GeH bond lengths fall in the range of 1.530–1.551 Å, which is in agreement with the experiment value (1.541 ± 0.006 Å) 39. For the Ge 2 H 6 anion, Tada and Yoshimura40 theoretically explored seven structures, including minima and saddle points, in 1992. They found that a C 2h isomer has the lowest energy using the HF and MP2/DZPD methods.…”
Section: Resultssupporting
confidence: 87%
“…The Hartree–Fock error is nonsystematic and always large, sometimes of the same order of magnitude as the bonding energy itself or even larger. Thus, most of the studies were performed at post-Hartree–Fock levels. , The MP2 level is satisfactory and provides geometries and bonding energies in good agreement with higher orders of perturbation theory. , …”
Section: Introductionmentioning
confidence: 99%
“…The results of a 29 Si ENDOR study were found to be hardly consistent with the ab inito π-type empty orbital model, suggesting a σ* Si-Si or Si 3d character of the SOMO in cyclopolysilane anion radicals, and ESR studies on analogous molecular systems lead to a representation of the SOMO as a linear combination of σ* Si-C and σ* Si-Si orbitals. According to recent ab initio studies at the MP4SDTQ level on the disilane and digermane radical anions, the SOMO is a heteroatom−heteroatom σ* antibonding orbital with a large heteroatom s diffuse orbital contribution, while the participation of Si 3d or Ge 4d orbitals is found to be negligibly small. We therefore have an uncertain picture of the low-energy unoccupied orbitals in such compounds.…”
Section: Introductionmentioning
confidence: 99%